Microencapsulation of Betacyanin extract from amaranth - Chong, Pik Han (2015)
Microencapsulation process is used to develop natural pigments by using a spray drying process. Betacyanins are red-violet natural pigment can be found in plant sources. In this project, the betacyanins were obtained from red amaranth. The optimization of spray drying process and types of encapsulating agents used are important to obtain desired pigment values. The objectives of the research are to investigate the effect of solvents on the yield and the colour properties of Amaranthus gangeticus and Amaranthus blitum, to examine the physicochemical properties and optimise spray drying conditions of maltodextrin-microencapsulated betacyanins as influenced by the inlet temperature and the maltodextrin concentration, to investigate the quality of β-cyclodextrin-encapsulated betacyanin pigment powder as influenced by spray drying conditions: inlet temperature, feed concentration and feed flow rate, and to investigate the drying parameters of spray-dried betacyanin pigment powder encapsulated by maltodextrin and β-cyclodextrin as influenced by spray drying conditions. Amaranth betacyanins are extracted from A. gangeticus and A. blitum by using water, methanol and ethanol extraction methods. Betacyanin content, total soluble solids and colour parameters are analyzed to assess extraction efficiency. A Principal Component Analysis is used to establish the relationships between the different analytical variables and to detect the most important factors of variability. The extracts are then microencapsulated by using a spray drying process. A Response Surface Methodology (RSM) was employed as a statistical analysis tool throughout the research. A. gangeticus extract (152.5 mg/100 g fresh weight) contains about two and half time more betacyanin with half of total soluble solids compared to A. blitum (62.1 mg/ 100 g of fresh weight). Water is the best as solvent for extracting betacyanin from A. gangeticus and ethanol in case of A. blitum. Three principal components are found among the seven analytical variables accounting 88% of total variability. The first principal component mostly reflects the redness, whereas the second principal component reflects the betacyanin content, total soluble solids and lightness. It is suggested that A. gangeticus is selected as raw material and extracted by water extraction method. The results for second objective show that betacyanin retention is affected by inlet temperature whereas antioxidant activity is influenced by maltodextrin concentration. Only the effect maltodextrin concentration is found to have a significant effect on colour value. Particle densities and sizes are slightly affected by the process conditions studied. For β-cyclodextrin was used as the encapsulating agent, the results reveal that all the studied physicochemical properties of betacyanin pigment powder are affected by the three spray drying operating conditions. The glass transition temperature and storage studies are carried out to ensure the powder stability. Results of drying parameters explain that the droplet size is influenced by inlet temperature for both encapsulating agents and β-cyclodextrin concentration remarkably affects the droplet size for β-cyclodextrin-encapsulated pigment. As a conclusion, using of β-cyclodextrin as encapsulating agent exhibits preferable results compared to maltodextrin. The research suggests that using of β-cyclodextrin as encapsulating agent for spray drying of betacyanins with proposed optimized formulation by RSM (Inlet temperature 190 °C, β-cyclodextrin concentration 13.89% and fee flow rate 9 ml/min) has potential to be utilized in food industries. The studied β-cyclodextrin-encapsulated betacyanin pigment can be applied to food system for future work.